Community-oriented Motivational Interviewing (MI): A novel framework extending MI to address COVID-19 vaccine misinformation in online social media platforms. (April 2023) - Scales, David; Gorman, Jack M.; DiCaprio, Peter; Hurth, Lindsay; Radhakrishnan, Malavika; Windham, Savannah; Akunne, Azubuike; Florman, Julia; Leininger, Lindsey; Starks, Tyrel J.
Abstract: Researchers have linked circulating misinformation in online platforms to low COVID-19 vaccine uptake. Two disparate literatures provide relevant initial guidance to address the problem. Motivational Interviewing (MI) effectively reduces vaccine hesitancy in clinical environments; meanwhile, social scientists note inoculation, rebuttal, and appeals to accuracy are persuasive in digital contexts. A tension is inherent in these approaches. MI in digital forums may induce an 'illusory truth effect, ' wherein falsehoods appear more accurate through repetition. Yet, rebutting misinformation directly may elicit backfire or reactance effects, motivating some to amplify their presentation of misinformation. Building on Identity Process Theory, we propose a theoretical framework for conducting MI-based infodemiology interventions among digital communities that conceptualizes the community in toto (rather than one specific person) as the unit of focus. Case examples from interventions on public Facebook posts illustrate three processes unique to such interventions: 1) Navigating tension between addressing commenters and "bystanders"; 2) Activating pro-vaccine bystanders; and 3) Reframing uncertainty or information individuals might find concerning or threatening according to implied collective values. This paper suggests community-oriented MI can maximize persuasive effects on bystanders while minimizing potential reactance from those with committed beliefs, thereby guiding community-oriented public health messaging interventions enacted in digital environments. Highlights: Infodemiologists addressing Covid-19 vaccine hesitancy online offer an opportunity to extend MI to community stakeholders. MI practitioners face tension avoiding reactance in a public audience balancing between committed believers and bystanders. Community-oriented MI re-positions the community as a whole as the focus of the intervention. Community-level resources like collective values and self-efficacy can be leveraged as sources of behavioral motivation. Providers can activate bystanders to manage conflict and propagate high-quality information to other networks. Abstract : Infodemiologist: @1 I understand how you can be worried about the vaccines. While they seem new, mRNA vaccine technology has been studied since the 2000's. Covid vaccine-related data is closely monitored so that plus data from other vaccines means the likelihood of long term side effects from COVID vaccine is very low. These vaccines have been well studied. Hydroxychloroquine does not really help improve covid outcomes. [NIH link] Thalidomide was a tragedy, and doesn't compare here because safety concerns were ignored for years. Covid vaccines are well researched and the data is publicly available. This link gives details of vaccines authorized in the US: they describe the trials and results from each phase. [CDC link and disclaimer].